2005
DOI: 10.1111/j.1475-6773.2005.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Short Form of the Patient Activation Measure

Abstract: Objective. The Patient Activation Measure (PAM) is a 22-item measure that assesses patient knowledge, skill, and confidence for self-management. The measure was developed using Rasch analyses and is an interval level, unidimensional, Guttman-like measure. The current analysis is aimed at reducing the number of items in the measure while maintaining adequate precision. Study Methods. We relied on an iterative use of Rasch analysis to identify items that could be eliminated without loss of significant precision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
1,770
10
32

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,511 publications
(1,842 citation statements)
references
References 5 publications
30
1,770
10
32
Order By: Relevance
“…Utilizing an objective risk assessment tool such as the Patient Activation Measure could help identify the patients who stand to benefit most from such interventions. 17 Our study has several strengths, including the large multicenter design, with data collection at the time of the readmission, and the inclusion of multiple physician viewpoints. There are also several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing an objective risk assessment tool such as the Patient Activation Measure could help identify the patients who stand to benefit most from such interventions. 17 Our study has several strengths, including the large multicenter design, with data collection at the time of the readmission, and the inclusion of multiple physician viewpoints. There are also several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Questions are rated on a 4-point Likerttype scale; possible scores range from 0, lowest activation, to 100, highest activation. PAM has strong psychometric properties, which include strong test-retest reliability and good internal consistency (α =.80) (Hibbard, Mahoney, Stockard, & Tusler, 2005) "people have adopted new behaviors but may not be able to maintain them in the face of life stress or health crises" (Chubak, 2012, Hibbard, Mahoney, Stockard et al, 2005, 2007.…”
Section: Methodsmentioning
confidence: 99%
“…eye examinations for people with diabetes, keeping diary of blood pressure readings), and control of chronic illness (e.g. HbA1c control, fewer hospitalizations) 13,14,[16][17][18][19][20] . Many of the studies are limited, however, by reliance upon self-reported health outcomes and use of relatively small samples.…”
Section: Introductionmentioning
confidence: 99%